Exploration of vitamin B12-producing bacteria from Indonesia Eutrophic Lake: A new strategy to improve microalgae biomass production - Prabaningtyas Sitoresmi; TRI ARDYATI; SUHARJONO SUHARJONO; CATUR RETNANINGDYAH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prabaningtyas S, Ardyati T, Suharjono, Retnaningdyah C. 2021. Exploration of vitamin B12-producing bacteria from Indonesia Eutrophic Lake: A new strategy to improve microalgae biomass production. Biodiversitas 22: 4538-4544. Biofuel producing autotrophs and heterotrophs organisms are mostly found in freshwaters such as lakes. Preliminary research showed that Ranu Grati has a high diversity of microalgae and bacteria. Microalgae are known as one source of biofuels due to the high content of lipid. The growth of microalgae is strongly influenced by vitamin B12, which is synthesized by bacteria. The role of vitamin B12 in the metabolism of algae is mainly as a co-enzyme for vitamin B12-dependent methionine synthase. The purpose of this research was to observe the bacterial diversity based on NGS analysis, to explore vitamin B12 produced by bacteria from Ranu Grati lake, and also to identify the highest potency of vitamin B12-producing bacteria based on 16S rRNA gene sequencing. The study was carried out by taking a water sample at a depth of 50 cm at five stations. Isolation of total bacterial DNA was carried out using FastDNA Spin Kit for Soil. The metagenomic method of Next Generation Sequencing (NGS) was used as an initial study of bacterial diversity. Vitamin B12-producing bacteria was isolated using PYBG agar (phytone peptone, trypticase peptone, lab-lemco powder, bacto yeast extract, glucose, agar). Isolated bacteria were screened for production of vitamin B12. The potential isolates were identified base on 16S rRNA gene sequence similarity. The results of the metagenomic study showed that the genus of potential bacteria producing vitamin B12 included Bacillus, Pseudomonas, Propionibacterium, Enterobacter, Escherichia, Acinetobacter, and Flavobacterium. The results of screening with PYBG media obtained 30 isolates of vitamin B12 producing bacteria. Ten efficient vitamin B12-producing isolates were identified as Lysinibacillus fusiformis (isolate G2V1), Bacillus cereus group (isolate G2V25, G2V24, G2V13, G2V9, G2V8), Alcaligenes faecalis (isolate G2V22), Delftia acidovorans (isolate G2V14A) and the genus Delftia (isolate G2V19). The isolate G2V1 (Lysinibacillus fusiformis) was the highest producer of vitamin B12 which was able to produce 33,783 ug/mL of vitamin B12 at 4 days incubation time.